Evaluation of efficacy of Amitriptyline vs. Gabapentin in diabetic peripheral neuropathy - Mala Chandra; Ravinder Garg; Jasleen Kaur; Santram; Navjot Kaur; Ranabir Pal (Al Ameen Medical College, 2017)
Background: The management of patients with Diabetic peripheral neuropathy (DPN) is challenging and often difficult to treat with current drug regime. Objective: To compare efficacy of Amitriptyline and Gabapentin in DPN. Methods: Patient screening and recruitment were carried out with diagnosis of DPN based on clinical history, complete physical examination and Michigan Neuropathy Scoring Instrument (MNSI) in this unicentric, prospective, open labeled, study with two parallel treatment arms. Following selection and recruitment, 100 adults aged 18 years and more, having MNSI score above 4 and Physical assessment part score above 2, were randomly assigned into two groups viz. Group A received oral Amitriptyline and Group B received oral Gabapentin for a duration of 12 weeks. The patients were examined four times during the study period. After the baseline visit, patients were asked to report at subsequent visits at 4 weeks interval up to 12 weeks. Efficacy was measured by using 11-point numeric pain rating scale and MNSI score. Results: On comparing both the treatment groups, the mean pain score reduction as per 11-point numeric pain rating scale was statistically significant at 4 weeks (p= 0.0025), 8 weeks (p=0.0109) and 12 weeks (p=0.0412) in between the two groups. This study shows statistically significant difference in reduction in mean pain score between the two groups. It was seen that Gabapentin reduces pain more significantly than amitriptyline at 4, 8 and 12 weeks (p<0.05) as per NPRS scale assessed on NPRS scale and PPR (4-point scale) across the time while Amitriptyline was associated with more adverse effects. Conclusions: Our study shows that Gabapentin relieves pain faster than amitriptyline with lesser adverse drug reaction.